Milrinone-induced postconditioning requires activation of mitochondrial Ca2+-sensitive potassium (mBKCa) channels - Behmenburg, Friederike; Berger, Marc Moritz (Journal of cardiothoracic and vascular anesthesia, 2018)
Objectives: Cardioprotection by postconditioning requires activation of mitochondrial large-conductance Ca2+-sensitive potassium (mBKCa) channels. The involvement of these channels in milrinone-induced postconditioning is unknown. The authors determined whether cardioprotection by milrinone-induced postconditioning involves activation of mBKCa channels in the rat heart in vitro. Design: Randomized, prospective, blinded laboratory investigation. Setting: Experimental laboratory. Participants: Male Wistar rats. Interventions: Hearts of male Wistar rats were randomized, placed on a Langendorff system, and perfused with Krebs-Henseleit buffer at a constant pressure of 80 mmHg. All hearts were subjected to 33 minutes of global ischemia and 60 minutes of reperfusion. At the onset of reperfusion, hearts were perfused with different concentrations of milrinone (0.3-100 μM) for determination of a dose-effect curve. In a second set of experiments, 3 μM milrinone was administered in combination with the mBKCa channel inhibitor paxilline (1 μM). Infarct size was determined by triphenyltetrazoliumchloride staining. Measurements and Main Results: In control animals, infarct size was 37 ± 7%. Milrinone at a concentration of 3 μM reduced infarct size to 22 ± 7% (p < 0.05 v control). Higher milrinone concentrations did not confer stronger protection. Paxilline completely blocked milrinone-induced cardioprotection whereas paxilline alone had no effect on infarct size. Conclusions: This study shows that activation of mBKCa channels plays a pivotal role in milrinone-induced postconditioning.
Available online 29 November 2017
Gesehen am 12.10.2018
Im Titel ist der Ausdruck "2+" hochgestellt
Im Titel ist der Ausdruck "Ca" tiefgestellt